Who perceives women's rights as threatening to men and boys? Explaining modern sexism among young men in Europe - Off, Gefjon; Charron, Nicholas; Alexander, Amy (Frontiers in Political Science, 2022)
While Western democracies have become increasingly gender-equal over the past decades, recent research documents a backlash against gender equality in the form of rising modern sexism. Previous research shows that modern sexism predicts political attitudes and voting behavior that are detrimental to women's empowerment and liberalism. Yet, we know little about which factors explain modern sexist attitudes and how they operate across multiple country contexts. Building on modern conceptualizations of sexism, we theorize that (perceived) increases in competition between men and women provoke modern sexism among young men in particular. Using an original measure that approximates dimensions of modern sexism embedded in the 2021 EQI survey, capturing 32,469 individuals nested in 208 NUTS 2 regions in 27 European Union countries, we demonstrate that young men are most likely to perceive advances in women's rights as a threat to men's opportunities. This is particularly true for young men who (a) consider public institutions in their region as unfair, and (b) reside in regions with recent increases in unemployment resulting in increased competition for jobs. Our findings highlight the role of perceived competition between men and women in modern sexism and contradict the argument that older generations are most likely to backlash against progressive values, potentially adding to research explaining the recent backlash against gender equality.